Development and Implementation of Projection-Based Installation in Gallery Space and Visitors Experience - Auzani Zeda, Mohamed Kassim; Hasnizam, Abdul Wahid; Muhyiddin, Mohammed (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In this paper, we present a projection-based installation designed for gallery-based exhibition. The installation system based on the Spatial Augmented Reality or known as "SAR," in which digital images were projected onto real objects or materials using projectors such as projection mapping techniques. This project studied the use of digital technology for gallery exhibition installation works to enrich and create an engaging audience's art experience through an immersive space created through SAR application. The study involved 79 youth who responded about their experience after viewing the projection-based installation work through a questionnaire survey. The findings show that the use of digital technology to the installation creates dreamlike scenes, imitating nature ambiance complemented with visuals and sound and well provides immersive experience among the visitors through the mixing of virtual images with real objects. The significance of this research on SAR application in exhibition artworks is essential to understand how it affects the audience's experience. The results are necessary as contributions for the development of innovative art mediums intended for gallery-based exhibitions and visitors' engagement, mainly targeted among the youth as the modern audience.